1993
DOI: 10.1254/jjp.61.283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SM-9018, a Potential Atypical Neuroleptic, on the Central Monoaminergic System in Rats

Abstract: ABSTRACT-This investigation was undertaken to characterize the vasoconstrictor responsiveness in aortas isolated from a rat model of arteriosclerosis induced by vitamin D2 (VD) administration followed by feeding with a high-cholesterol diet. Cumulative contractile responses to KC1, noradrenaline and serotonin in thoracic aortic strips isolated from arteriosclerotic rats were slightly augmented in concentrations lower than the EC50 value of each agent and rather attenuated in their higher concentrations as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…In the second set of experiments, we examined the effect of concurrent Warfarin treatment in an animal model in which some degree of artery calcification had been induced by high doses of vitamin D. Treatment with high doses of vitamin D has been known for many years to induce artery calcification in humans, rats, and other animals. [32][33][34][35][36][37] This vitamin D-induced calcification is confined to the media of arteries and closely resembles the pattern of calcification seen in Monckeberg's syndrome in humans. 24,25 In the vitamin D treatment regime used for the current studies, vitamin D induced marked artery calcification within 4 days of treatment.…”
supporting
confidence: 58%
“…In the second set of experiments, we examined the effect of concurrent Warfarin treatment in an animal model in which some degree of artery calcification had been induced by high doses of vitamin D. Treatment with high doses of vitamin D has been known for many years to induce artery calcification in humans, rats, and other animals. [32][33][34][35][36][37] This vitamin D-induced calcification is confined to the media of arteries and closely resembles the pattern of calcification seen in Monckeberg's syndrome in humans. 24,25 In the vitamin D treatment regime used for the current studies, vitamin D induced marked artery calcification within 4 days of treatment.…”
supporting
confidence: 58%
“…Similarly, this was attributed to calcium deposition in the vascular wall [19]. A negative correlation between maximal contraction and calcium content was also found in aorta from vitamin-D-treated rats fed with a normal or high-cholesterol diet [38]. On the other hand, some studies have shown that vitamin D treatment increases blood vessel response to vasoconstrictors.…”
Section: Vasoactivitymentioning
confidence: 87%
“…This is not entirely surprising, since the rat is relatively resistant to atherosclerosis [3], so that most rat models of diet induced cardiovascular disease employ susceptible strains of rat [4][5][6][7] or vitamin D [8,9]. We wished to develop a simple model of vascular dysfunction, based only on a highcholesterol diet.…”
Section: Discussionmentioning
confidence: 99%
“…The rat is relatively resistant to atherosclerosis [3], so that consistent morphological changes in the vascular wall are reported only when combining a high cholesterol diet with vitamin E deficiency [5], excess vitamin D [8], excess total fat [7] or with models of hypertension [6]. In a study of normal rats fed a 2% cholesterol and 5% fat diet for 6 months, structural changes in the aorta were only found in aged (24 month old) rats [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation